PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR PKn PADA SISWA KELAS VIII SMP NEGERI 1 KLABANG: SMP NEGERI 1 KLABANG BONDOWOSO - HISWARI ELLY UTAMI (Dewan Pendidikan Bondowoso, 2021)
The purpose of this study was to determine the improvement of Civics learning outcomes through the Problem Based Learning (PBL) model for class VIII students of SMP Negeri 1 Klabang Bondowoso. This research is a classroom action research conducted by researchers by trying to apply the Problem Based Learning learning model. This classroom action research consists of a series of four activities carried out in an iterative cycle. namely: (1 Planning (2 Actions 3) Observation, and 4) Reflection. This classroom action research was conducted at SMP Negeri 1 Klabang which is located at Jalan Jl. Blimbing No. 10 Klabang, Kec. Klabang, Kab. Bondowoso Postal code: 68284 for 3 months, starting from September 2019 to November 2019. The object of this research is class VIII students of SMP Negeri 1 Klabang Bondowoso in the Odd semester of the 2019/2020 academic year in Civics subjects with Human Rights material. Based on the results of the research and discussion, it can be concluded that the use of problem based learning learning models in Civics Education (PKn) learning on human rights materials can improve learning outcomes for class VIII students of SMP Negeri 1 Klabang Bondowoso in the odd semester of the 2019/2020 school year. seen from data 1). Mastery learning, in the pre-cycle the amount of student learning mastery is 43.75%, in the first cycle it increases to 68.75%, while in the second cycle it increases to 81.25%, 2) Student absorption in the pre-cycle is 61.26%, in the first cycle it increases to 68.59 in the second cycle increased to 76.09%.